PEMBUATAN GAME ARCADE “CITY PROTECTOR” DENGAN MENGGUNAKAN TOUCH GESTURE RECOGNIZER - Andrean Danawan; Jeanny Pragantha; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
City Protector is an Arcade Tower Defense Game with endless element. This game implements touch gesture recognizer feature. This game is developed with Unity game engine and playable in Android-based smartphone. To kill zombies, players must draw the symbols contained in the explosives that brought by zombies. Testing is done by blackbox testing, alpha testing, and beta testing through a survey of 32 respondents. The results indicate that City Protector has interesting features and gameplay concepts. It is provides new experiences because the Touch Gesture Recognizer feature is rarely found in general.